Evaluation of Maternal Health Related Government Schemes being provided to the High-Risk Mothers of Bhavnagar District, Gujarat - Pooja A Chauhan; K D Bhalani (Medsci Publications, 2019)
Background: About 20-30% of all the pregnancies belong to the high-risk category.This study conducted to evaluate maternal  health related government schemes being provided to the high-risk mothers of Bhavnagar district, Gujarat. Methods: It was a cross-sectional study conducted among the high- risk mothers of Bhavnagar district during the period from March 2017 to August 2018. 10 PHCs were selected using PHC score card. From each selected PHCs, 3 sub centres were selected randomly. From each selected sub centre, 3 high-risk mothers were randomly selected and interviewed. Results: Among the eligible high-risk mothers, 53.3% mothers of the worst performing and 72% mothers of the best performing PHCs received cash assistance under JSY. All the eligible mothers from the worst performing PHCs received benefits under KPSY, while in the best performing PHCs, 87.5% of the eligible mothers received benefit for early registration and 83.3% of the eligible mothers received benefit for institutional delivery under KPSY. Some of the mothers didn't receive the cash assistance under JSY because of issues related to their bank account and few others didn't receive the benefit even after fulfilment of all the require- ments of the scheme and they were not aware about the reason.